Auditory Mismatch Negativity Response in Institutionalized Children - Ovchinnikova, Irina; Zhukova, Marina A.; Luchina, Anna; Petrov, Maxim V.; Vasilyeva, Marina J.; Grigorenko, Elena L. (Frontiers in Human Neuroscience, 2019)
The attunement of speech perception/discrimination to the properties of one’s native language is a crucial step in speech and language development at early ages. Studying these processes in young children with a history of institutionalization is of great interest, as being raised in institutional care (IC) may lead to lags in language development. The sample consisted of 82 children, split into two age groups. The younger age group (<12 mos) included 17 children from the IC and 17 children from the biological-family-care (BFC) group. The older group (>12 mos) consisted of 23 children from the IC group, and 25 children from the BFC group. A double-oddball paradigm with three consonant-vowel syllables was used, utilizing the native (Russian) and foreign (Hindi) languages. A Mismatch Negativity component was elicited within a 125-225 ms time window in the frontal-central electrode. Findings demonstrate the absence of MMN effect in the younger age group, regardless of the living environment. Children in the older group are sensitive to native deviants and do not differentiate foreign language contrasts. No significant differences were observed between the IC and BFC groups for children older than 12 months, indicating that children in the IC have typical phonological processing. The results show that the MMN effect is not registered in Russian speaking children before the age of 12 months, regardless of their living environment. At 20 months of age, institutionally reared children show no evidence of delays in phonetic development despite ​limited experience of language.